Prarancangan Pabrik Akrilonitril Menggunakan Proses Sohio Dengan Disain Alat Utama Kolom Absorber (A-101) - Natalia Natalia; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrylonitrile has the potential to be used as an additive in the chemical industry including the manufacture of thermoplastics, adiponitrile for the nylon industry, acrylamide, resin, synthetic rubber, acrylic fibers for the acrylic fabric industry and ABS (Acrylonitrile Butadiene Styrene) resin for the manufacture of plastic goods. The use of acrylonitrile which is quite varied makes acrylonitrile needed in large quantities in Indonesia. Based on data from the Central Statistics Agency for the past 5 years, the demand for acrylonitrile in Indonesia is between 1000-6000 tons/year. Acrylonitrile is produced by the Sohio process using propylene, ammonia and air as raw materials. The acrylonitrile plant operates for 300 days per year in 24 working hours per day with a production capacity of 128,000 tons/year. This factory produces acrylonitrile with a purity of 99.47% as the main product while the byproducts are acetonitrile and hydrogen cyanide. The location of the acrylonitrile plant establishment is planned in the Basilam Baru area, Sungai Sembilan District, Dumai City, Riau Province. The design of the main tool of the absorber column (A-101) is useful for separating ammonia gas that is not completely converted from the resulting product using sulfuric acid as a solvent. Unneutralized ammonia causes ammonia to react with acrylonitrile to form various impurity and acid precipitates to polymerize hydrogen cyanide. This absorption process will produce Ammonium Sulphate. The absorber column with packed bed column has a height of 4.2084 m with a column diameter of 0.5588 m. The type of packing used is rasching ring made of ceramic which is shaped like a hollow cylinder ring with a size of 4 in with a torispherical flanged dished head. Fixed Capital Investment (FCI) of this acrylonitrile plant is $ 59,018,469.7 and Working Capital Investment is 15% of Total Capital Investment (TCI) of $ 10,415,024.1 so that the Total Capital Investment (TCI) value is $ 69,433,493 ,7. The total production cost of the acrylonitrile plant is $226,071,844.0 while the net profit after tax is 35%, which is $406,667,476 and the net cash flow of the acrylonitrile plant is $408,880,669. Return on Investment (ROI) after tax is 59.54%, Pay Out Time (POT) is 1.57 years and Break Event Point (BEP) is 35%. The IRR value of the acrylonitrile factory is 22.67% greater than the bank's RRR value of 22.55%, and the Net Present Flow (NPV) value of $ 2,504,738,736.6 is greater than the Total Capital Investment (TCI) value. From the economic analysis, the acrylonitrile plant is feasible to establish. Keywords: absorber, acrylonitrile, packed bed column, propylene, sohio process